ANALISIS POTENSI PAJAK DAERAH DAN RETRIBUSI DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KABUPATEN HALMAHERA UTARA - Hehega, Meilin; Karamoy, Herman; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2018)
This study aims to analyze the types of local taxes and user charges on the growth and contribution to total taxes and levies. Identify into prime, potential, growing and underdeveloped classifications. The data used are primary and secondary data in North Halmahera Regency with research period of 2012 – 2016. Analyzer used is growth analysis, contribution analysis and overlay analysis. The results of this study indicate that the growth and contribution of types of taxes and levies fluctuated during the 5-year budget. Based on the analysis of restaurant tax overlay and levy building permit is a type of local tax that has the potential to be developed in order to increase local revenue.Keywords: growth, contribution, potential of local taxes and levies